Statistical approach to identify variables predicting sulphide clay occurrence in southern Finland - Saresma Maarit; Löfman Monica; Kosonen Emilia; Ojala Antti E K; Korkiala-Tanttu Leena (SPRINGER HEIDELBERG, 2025)
Acid sulphate soil and sulphide-bearing sediments cause various challenges in construction projects and land use planning, as well as harmful environmental effects. Fine-grained sulphide sediments were mainly formed in coastal areas during the Litorina Sea water phase at approximately 7000 BP in the capital region of Finland, but not all these sediments contain sulphide clay. In this study, environmental and material property variables related to the depositional conditions of sulphide clay were selected for statistical analyses to find their association with the occurrence of sulphide. The datasets consisted of sulphide investigations by the City of Espoo, the City of Helsinki, and the Geological Survey of Finland. Statistically significant associations were found in the study area between the occurrence of sulphide and enumerative variables (i.e., sediment organic content, total clay depth, topographic class in the Litorina Sea phase, and water depth) in the Litorina Sea phase. Locations where sulphide clay is especially likely to occur consist of organic-rich (>= 2%) thick clay (>= 15 m) deposits in a topographically narrow depression with deep Litorina water (>= 30 m), or where there is a moderate depth clay (3-5 m) in a local depression with shallow Litorina water (10-20 m). The best individual predictor for sulphide clay occurrence in the study area was found to be the sediment organic content, and, together with sediment water content, these variables very accurately predicted the occurrence of sulphide clay. In addition, clay depth is a very good predictor and, together with the topographic class narrow depression and the Litorina water depth or current elevation, can be used to predict sulphide occurrence.